Semiotic Perspectives of Indonesian Horror Movie Posters - Komang Widya Udiani Dewi; Desak Putu Eka Pratiwi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research investigates the semiotic dimensions of horror movie posters and how they use signs and pictures to communicate their genre-specific messages. The poster was selected for a popular horror movie in Indonesia. The verbal and visual signs on these posters were analyzed using semiotic theory as explained by Chandler (2007), studying the meaning of verbal and visual signs in terms of connotative and denotative meaning by Barthes (1968) and Cerrato's (2012) theory for interpreting the meaning of colors. Observation and note-taking techniques were used to collect data for this study. The data of this research was analyzed using the descriptive qualitative method. This research shows that selected posters effectively use dark, sinister imagery and bold, jagged typography to convey their horror themes. For instance, the use of a giant skull formed by twelve wrapped corpses in the “Siksa Kubur” poster creates a ghoulish and creepy image that resonates with cultural fears of death and the supernatural. The posters expressed both connotative and denotative meanings. Combining these elements creates a persuasive and engaging narrative that resonates with the cultural and supernatural themes prevalent in Indonesian horror. The posters, beyond being elements of the story, also act as marketing tools, effectively capturing and holding the audience's attention by using meaningful cultural symbols and emotions. These discoveries have important implications for filmmakers and marketers, indicating that a thorough grasp of cultural semiotics can improve horror films' narrative impact and market appeal.